2013
DOI: 10.3171/2013.2.focus12397
|View full text |Cite
|
Sign up to set email alerts
|

Integration of functional neuronavigation and intraoperative MRI in surgery for drug-resistant extratemporal epilepsy close to eloquent brain areas

Abstract: Object The authors performed a retrospective study to assess the impact of functional neuronavigation and intraoperative MRI (iMRI) on surgery of extratemporal epileptogenic lesions on postsurgical morbidity and seizure control. Methods Twenty-five patients (14 females and 11 males) underwent extratemporal resections for drug-resistant epilepsy close to speech/motor brain areas or adjacent to white matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 52 publications
1
52
0
Order By: Relevance
“…Again, our reported rates of 36% transient and no permanent new neurological deficits in the iMRI cohort are consistent with those of Sommer et al, who reported 20% transient and 12% permanent neurological deficits in their cohort of iMRI-resected extratemporal epilepsy adjacent to eloquent cortex. 32 Importantly, this represents a reduction in deficits over conventional resections in our study, and in previous studies that have reported postoperative neurological deficits ranging from 50% to 83%. [1][2][3]25 Hence, our results demonstrate that iMRI-assisted resections are less prone to incurring neurological deficits.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Again, our reported rates of 36% transient and no permanent new neurological deficits in the iMRI cohort are consistent with those of Sommer et al, who reported 20% transient and 12% permanent neurological deficits in their cohort of iMRI-resected extratemporal epilepsy adjacent to eloquent cortex. 32 Importantly, this represents a reduction in deficits over conventional resections in our study, and in previous studies that have reported postoperative neurological deficits ranging from 50% to 83%. [1][2][3]25 Hence, our results demonstrate that iMRI-assisted resections are less prone to incurring neurological deficits.…”
Section: Discussionmentioning
confidence: 48%
“…Using iMRI in conjunction with functional MRI and diffusion tensor imaging (DTI), Sommer et al previously reported achieving GTR in all patients and 72% complete seizure freedom in resection of lesional epilepsy in close proximity to eloquent cortex. 32 Of note, their cohort consisted of 7 (28%) of 25 patients with intractable epilepsy secondary to FCD (1 Type IIA and 6 Type IIB), with the remainder of the cases secondary to mixed etiology including posttraumatic glial scars and cavernous hemangiomas. Importantly, surgical outcomes in our study are consistent with those reported by Sommer et al and considerably improved over conventional resection both in our current study and in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,8,9,21,24,25 Our objective in this study was to assess the impact of iMRI on intraoperative evaluation, surgical course of reabbreviations ECoG = electrocorticography; FCD = focal cortical dysplasia; iMRI = intraoperative MRI; OE = operative event; OR = operating room; SPGR = spoiled gradient echo recalled; 3DGM = 3D gyral map. obJective Previous meta-analysis has demonstrated that the most important factor in seizure freedom following surgery for focal cortical dysplasia (FCD) is completeness of resection.…”
mentioning
confidence: 99%